Promoting green infrastructure in Mexico's northern border: The Border Environment Cooperation Commission's experience and lessons learned - Giner, Maria-Elena (2019)
This paper describes the application of a comprehensive strategic approach for integrating Green Infrastructure (GI) in urban planning in Mexican communities along the U.S-Mexico border as a means to mitigate the environmental, economic, and social impacts of inadequate stormwater management. Population growth and extended urban footprints in the region's cities have decreased rainfall infiltration and significantly increased runoff, carrying sediments and other pollutants into binational watersheds thus contributing to the pollution of aquatic habitats and potable water sources. As a strategy to mitigate these impacts, the Border Environment Cooperation Commission (BECC) developed a four year initiative with the long-term goal to support communities in building resiliency through the use of GI in public spaces such as parks, sidewalks, medians, and parking lots as a way to adapt to climate change, improve urban image, and strengthen native ecosystems. The Border Green Infrastructure Initiative was organized around training, strengthening municipal codes, developing pilot projects, restoring native vegetation, and the participation of residents, local government, and the private sector. The investment over the entire period was ap- proximately USD$800,000. Outcomes were noteworthy. Approximately 900 professionals received various types of capacity building. Five cities and four Mexican border states were active participants in the program. Six pilot projects were implemented, three of which could capture a total volume of 4691m3 of water in one year. In two sites the annual sediment collected was 656m3. Finally, six technical tools were developed to assist communities in analysis and implementation. This approach represents a paradigm shift from the conventional management of stormwater through gray infrastructure and is intended to influence public policy at the local level, in a replicable and scalable way, resulting in more livable cities, improved water quality, and stronger binational environmental health.